태양광 발전소의 Snail trail 열화 현상과 출력 손실의 영향성 분석 - 오원욱(Oh Wonwook); 김대성(Kim Daesung); 전성근(Jeon Seonggeun); 윤아영(Yoon Ayoung); 김남승(Kim Namseung); 김상수(Kim Sangsoo); 서근원(Seo Kun Won); 최훈주(Choi hoonjoo) (한국태양에너지학회 논문집, 2020)
The snail trail is a common degradation phenomenon that is observed in solar power plants. Although the occurrence of cosmetic problems has been reported in previous studies, the contribution of these problems to the actual power loss is negligible. However, the cracking of the solar cell induces a loss in the output. We analyzed the results of the thorough investigation of a 95 kWp solar power plant that was operated in the field for 5 years. The snail trail phenomenon was observed in a specific module using current-voltage measurement, electroluminescence analysis, and visual inspection. We evaluated the impact of the loss in the generated power via image extraction. KCI Citation Count: 0